1995
DOI: 10.1590/s0034-89101995000200004
|View full text |Cite
|
Sign up to set email alerts
|

Preferencia de hospedadores de Culicidae (Diptera) recolectados en el centro de la Argentina

Abstract: Con el propósito de estudiar la preferencia de hospedadores vertebrados por mosquitos hembras, durante 2 períodos octubre-abril (primavera-verano), se realizaron muestreos cada 15 días en Córdoba y Cosquín (Argentina). Se utilizaron trampas de latón con cebo animal: anfibios (sapos), aves (pollos), mamíferos (conejos) y reptiles (tortugas). El 92,9% de los especímenes recolectados pertenecen al género Culex, mientras que un 7,0% corresponde a Aedes y el 0,02% restante a Psorophora ciliata, única especie que se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 16 publications
2
19
1
2
Order By: Relevance
“…scapularis and Cx. interfor ) infected with Genotype VII frequently feed on mammals hosts [20], [23]–[25]. Our data support the hypothesis that some SLEV strains are being maintained through alternative rodents-mosquitoes transmission cycles [14].…”
Section: Discussionsupporting
confidence: 81%
“…scapularis and Cx. interfor ) infected with Genotype VII frequently feed on mammals hosts [20], [23]–[25]. Our data support the hypothesis that some SLEV strains are being maintained through alternative rodents-mosquitoes transmission cycles [14].…”
Section: Discussionsupporting
confidence: 81%
“…While the source mosquito, Culex chidesteri , has not been shown to be a disease vector, WNV has been isolated from this species (Kent et al ., 2010b). Field studies have indicated this mosquito feeds on a range of hosts including humans, chickens, rabbits, and turtles (Almiron & Brewer, 1995). The NHUV isolate is part of a novel group of flaviviruses that we are tentative designating as unidentified vertebrate host (UVH) viruses that have been isolated from a wide geographic range including China (Wang et al ., 2009), Republic of Korea (Lee et al ., 2013a), Côte d’Ivoire (Junglen et al ., 2009), Finland (Huhtamo et al ., 2009), Israel (Kolodziejek et al ., 2013) and Peru (Evangelista et al ., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These species are numerous in locations where there are avian hosts, humans and horses. They feed primarily on birds, but also will feed on mammals and humans (Almiron and Brewer 1995). However, natural feeding patterns of these species of mosquitoes in Argentina have not been studied.…”
Section: Discussionmentioning
confidence: 99%